The effect of foreign language enjoyment on willingness to communicate among Chinese EFL students: conscientiousness as a mediator - Zhao, Jin; Guan, Kaining; Feng, Yu; Liu, Ziqing (Frontiers in Education, 2024)
IntroductionAn increasing body of research has explored the predictive effect of personality traits and affective factors on EFL learners’ willingness to communicate (WTC). However, more is needed to know about how the sub-facets of individual personality traits influence WTC in the classroom context. Therefore, drawing on positive psychology, this study aims to bridge this gap by examining these roles in a mediation model of WTC incorporating FLE and conscientiousness.MethodsTo this end, 244 Chinese EFL undergraduates from two distinct universities participated in an online survey, completing a composite questionnaire of the three constructs. The bootstrapping technique was employed to test the proposed relationships.ResultsThe findings indicated a positive correlation between both FLE and conscientiousness with WTC. Additionally, conscientiousness significantly mediated the relationship between FLE and WTC, supporting a partial mediation effect. Also, FLE had a direct influence on conscientiousness. These results may have some notable implications for EFL educators.DiscussionThe adoption of a holistic approach that emphasizes affective factors alongside acknowledging individual differences among learners could enhance students’ willingness to communicate in English.